Environmental management system and organizational performance in Malaysian manufacturing industry - Mohd Fuzi, Nursyazwani; Habidin, Nurul Fadly; Adam, Sabrinah; Ong, Sharon Yong Yee (Human Resource Management Academic Research Society, 2021)
The aim of this conceptual paper is to review the relationship between environmental management system and organizational performance in Malaysian manufacturing industry. The paper is prepared by reviewing the relevant literatures on environmental management system and organizational performance. The framework will provide a guide to Malaysian manufacturing industry to improve the environmental management system and organizational performance. The conceptual framework developed in this study can be used as a guideline to implement the environmental management system and organizational performance in Malaysian manufacturing industry. Thus, a conceptual framework of the importance of environmental management system and organizational performance, can serve to guide future research.